A single-beam positron emission computerized tomography study of trichotillomania in terms of cognitive behaviour therapy - Gordon, Charmaine (My University, 2008)
ABSTRACT Trichotillomania was first defined over a hundred years ago as a self inflicted alopecia resulting from avulsion of hair. Previous Positron Emission Tomography (PET) studies have shown increased count density in the right superior parietal region of patients suffering from trichotillomania. It is unclear if this increase in count density might be a state or trait related marker of the disease. Research has indicated that Cognitive Behaviour Therapy can systematically modify cerebral metabolic activity which is significantly related to clinical outcome. In the case of Obsessive Compulsive Disorder (OCD), a decrease of metabolic activity has been demonstrated using Pet. The present study was undertaken to investigate whether similar metabolic changes as indicated by Single Beam Positron Emission Computerised Tomography. (SPECT), will be found in trichotillomania after Cognitive Behaviour Therapy. Twelve patients diagnosed as suffering from trichotillomania, using DSM-IV criteria, underwent brain SPECT scanning using 99mTc-HMPAO. Scanning was performed before and after Cognitive Behaviour Therapy intervention. The psychotherapy was conducted in 12-16 sessions. The response to Cognitive Behaviour Therapy was assessed using the Psychiatric Institute Trichotillomania Scale and the Hamilton Anxiety Rating Scale. Ratings were completed at the beginning and end of the trial. The analysis of the scan data was done by comparing the left to the right superior parietal region. For each patient the region of interest was applied on the superior transaxial brain slices where the cingulate gyrus fully appeared. Each region of interest had the average number of counts normalised to the maximal cerebellar uptake. Baseline studies showed a significant increased count of 99mTc-HMPAO in the right superior parietal areas compared to the same areas on the left (p<0.0003). This pattern normalised after Cognitive Behaviour Therapy, such that there was no significant difference between the right and left superior parietal areas in those patients who responded (n=9) to therapy. In the non-responder group (n=3), the pattern remained unchanged. Using SPECT this study confirms previous reports of increased density in the right superior parietal lobe. In addition, it suggests that the increased count of 99mTc-HMPAO in the right parietal area is a state related disturbance in neurophysiology in this disorder, as it resolves with successful treatment. Of substantial importance is the fact that this study demonstrates a neurophysiological substrate and impact of psychotherapy. In conclusion this data suggests that the increased count density in the right superior parietal area is a state related marker of trichotillomania. 99mTc-HMPAO brain SPECT can therefore be used to monitor therapy of patients suffering from this disease.
Keywords: SPECT; trichotillomania; cognitive behaviour therapy